KONSEP PENGATURAN HUKUM TENTANG PERPINDAHAN NARAPIDANA ANTAR NEGARA (TRANSFER SENTENCED PERSON) STUDI KOMPARATIF ANTAR NEGARA - Rahmat, Fabitul; Muhibbin, Moh.; Parmono, Budi (Fakultas Hukum Universitas Hang Tuah, 2024)
In the international context, the transfer of sentence persons is regulated in the general international standards in handling cross-border crime issues as outlined in the 2000 Palermo Convention (United Nations Convention Against Transnational Organized Crime) which Indonesia passed into law through Law Number 5 of 2009 concerning the Ratification of the United Nations Convention Against Transnational Organized Crime, in which member states are allowed to make agreements in handling crime through extradition agreements, mutual legal assistance in criminal matters, and transfer of sentence persons. Legal regulation on the transfer of prisoners between countries (Transfer Sentenced Person (TSP)) is important for Indonesia in order to reform and social rehabilitation for prisoners, so that imprisonment is used to ensure, as far as possible, the reintegration of prisoners in society after release so that they can live a law-abiding and independent life. The need for the state to establish a regulation in the form of a law on the transfer of prisoners between countries (TSP), is intended to create legal certainty, so that cooperation carried out with other countries either as a country requested by Indonesia or vice versa (as a requesting country) has a legal basis that provides restrictions on what is in accordance with the concept of the purpose and politics of punishment law in Indonesia.